2020
DOI: 10.1177/1934578x20970855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Schisandra chinensis Extract on the Learning and Memory Ability of Mice With Learning and Memory Disorders

Abstract: The effect of Schisandra chinensis extract (SCE) on the learning and memory ability of mice with learning and memory disorders was investigated. After mice were given SCE prophylactically, different methods were used to establish mouse learning and memory disorders, and the radial maze test was used for the observation of SCE on the learning and memory ability of mice with learning and memory disorders. A mouse aging model was established by subcutaneously injecting d-galactose. The antiaging, antifatigue, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Superoxide dismutase activity, which is produced as a byproduct of oxygen metabolism and causes cell damage if not regulated, significantly improved after lignan extract treatment. Therefore, it was concluded that lignans can be used clinically as an agent that will exhibit an antiaging function by the regulation of oxygen metabolism and protein expression [ 210 ].…”
Section: Polyphenols On Agingmentioning
confidence: 99%
“…Superoxide dismutase activity, which is produced as a byproduct of oxygen metabolism and causes cell damage if not regulated, significantly improved after lignan extract treatment. Therefore, it was concluded that lignans can be used clinically as an agent that will exhibit an antiaging function by the regulation of oxygen metabolism and protein expression [ 210 ].…”
Section: Polyphenols On Agingmentioning
confidence: 99%